2022
DOI: 10.1007/s11095-022-03249-3
|View full text |Cite|
|
Sign up to set email alerts
|

Construction and Functional Evaluation of a Three-Dimensional Blood–Brain Barrier Model Equipped With Human Induced Pluripotent Stem Cell-Derived Brain Microvascular Endothelial Cells

Abstract: Purpose The purpose of this study was to construct and validate an in vivo three-dimensional blood–brain barrier (3D-BBB) model system equipped with brain microvascular endothelial cells derived from human induced pluripotent stem cells (hiPS-BMECs). Methods The 3D-BBB system was constructed by seeding hiPS-BMECs onto the capillary lane of a MIMETAS OrganoPlate® 3-lane coated with fibronectin/collagen IV. hiPS-BMECs were incubated under continuous switchba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 55 publications
(58 reference statements)
2
49
0
Order By: Relevance
“…BMECs cultured in this system expressed BBB markers such as Claudin-5, ZO-1, Glut-1 and Breast Cancer Resistance Protein (BCRP) and exhibited low permeability to LY. Notably, the authors found that ABCG2 (gene encoding BCRP) expression in BMECs was 3.3-fold higher in their 3D system compared to 2D monolayer culture measured by qRT-PCR, and that transport of BCRP substrates in their 3D system was comparable to that in previous in vivo rat studies (Kurosawa et al, 2022). It is possible that these systems could be further improved and lead to better in vitro BBB models if coatings alternative to C4/Fn were tested and optimized.…”
Section: Stem Cell-based Bbb Modelsmentioning
confidence: 81%
“…BMECs cultured in this system expressed BBB markers such as Claudin-5, ZO-1, Glut-1 and Breast Cancer Resistance Protein (BCRP) and exhibited low permeability to LY. Notably, the authors found that ABCG2 (gene encoding BCRP) expression in BMECs was 3.3-fold higher in their 3D system compared to 2D monolayer culture measured by qRT-PCR, and that transport of BCRP substrates in their 3D system was comparable to that in previous in vivo rat studies (Kurosawa et al, 2022). It is possible that these systems could be further improved and lead to better in vitro BBB models if coatings alternative to C4/Fn were tested and optimized.…”
Section: Stem Cell-based Bbb Modelsmentioning
confidence: 81%
“…However, SLC7A3 has low expression levels in iPSC-derived BMEC-like cells, mouse brain endothelial cells [ 66 ], and human endothelial cells [ 67 ] compared to the relatively higher expression of SLC7A1 . Further, SLC7A1 is highly and selectively expressed in brain endothelial cells with respect to other neurovascular cell types in single-cell RNA-sequencing datasets [ 66 ], and CAT-1 has previously been shown to be functionally active in iPSC-derived BBB models [ 68 , 69 ], marking it as an interesting candidate for further evaluation.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…As discussed in previous sections, such new technology has not yet yielded clinically relevant systems and results regarding brain penetration of molecules. However, recent advancements in brain organ on chip or 3D platforms (Piantino et al., 2022) using human‐induced pluripotent stem cell‐derived BMEC provided promising results (Kurosawa et al., 2022). However, more research needs to be conducted in this area to have a complete model that will be fit for disease pathology understanding as well as the function of BBB transporters.…”
Section: Future Perspectivementioning
confidence: 99%